ISU-ISU KONTEMPORER HUKUM BISNIS SYARIAH (MONOPOLI DALAM BISNIS SYARIAH) - Dadi Permana Putra (IAIN Ambon, 2018)
Monopoly and oligopoly, monopsy, dominant position, and various other forms of unfair competition in the world of commerce. Indeed the market is an economic element that can realize the benefit and welfare of human life. Islam forbids unfair competition and closes all roads leading to it. Goods and services that are community needs are never justified to be monopolized. In the view of Islam monopoly is something that is legal. What is not permitted in Islam is monopolistic behavior that can harm society.